2020
DOI: 10.21203/rs.3.rs-93178/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosomal miR-186 Derived from BMSCs Promote Osteogenesis Through Hippo Signaling Pathway in Postmenopausal Osteoporosis

Abstract: Background: Postmenopausal osteoporosis (PMO) that results from estrogen withdrawal is the most common primary osteoporosis among older women. However, little is known about the mechanism of PMO, and effective treatment of PMO is limited.Methods: We used qPCR, western blotting, and RNA pull down to investigate the relationship between miR-186 and Mob1. Also we investigated the effect of exosome in osteogenesis using ALP staining. And HE staining was used to verify the osteogenesis in PMO model.Results: Exosoma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These special features allow exos to play a regulatory role in certain diseases. The functional effects of exosomal miRNAs in OP have been well documented (Table 1) [52,[78][79][80][81]. Li et al reported that exos derived from MSCs can effectively ameliorate the development of OP, and exosomal miR-186 participates in this regulatory process [81].…”
Section: Role Of Exosomal Mirnas In Opmentioning
confidence: 99%
See 1 more Smart Citation
“…These special features allow exos to play a regulatory role in certain diseases. The functional effects of exosomal miRNAs in OP have been well documented (Table 1) [52,[78][79][80][81]. Li et al reported that exos derived from MSCs can effectively ameliorate the development of OP, and exosomal miR-186 participates in this regulatory process [81].…”
Section: Role Of Exosomal Mirnas In Opmentioning
confidence: 99%
“…The functional effects of exosomal miRNAs in OP have been well documented (Table 1) [52,[78][79][80][81]. Li et al reported that exos derived from MSCs can effectively ameliorate the development of OP, and exosomal miR-186 participates in this regulatory process [81]. Moreover, a recent study demonstrated that exosomal miR-1263 derived from human umbilical cord MSCs can inhibit osteoblast apoptosis and that nanomaterials loaded with miR-1263 may be ideal alternatives for the treatment of bone resorption disorders [80].…”
Section: Role Of Exosomal Mirnas In Opmentioning
confidence: 99%